Alterações hepáticas em aves domésticas (Gallus gallus domesticus): estudo retrospectivo e prospectivo de 300 casos - Marcelo Coelho Lopes (2021)
Brazil stands out worldwide in the production and breeding of poultry; however, several aspects regarding major diseases that affect poultry are not fully understood, including liver diseases. The present study aimed to assess the occurrence and the frequency of hepatic changes in poultry including broilers (B), layer hens (LH) and backyard poultry (BP). A retrospective and prospective study was conducted with data from the diagnostic service of the pathology sector (last 15 years), with a total of 300 cases with diagnoses of liver disorders. Industrial poultry (B and LH) were frequent affected (88%) and noninfectious changes were the most commonly diagnosed (69%). Considering etiology, the frequency of hepatic changes was classified as follows: degenerative changes (42%), bacterial (28%), metabolic (15%), toxic (8%), viral (3%), neoplastic (2%), as well as protozoal diseases (1,5%) and circulatory disorders (0,5%). Regarding the type of bird, degenerative, toxic changes and viral hepatitis were more frequent in broilers. Circulatory and metabolic disorders, as well as bacterial hepatitis, were more frequently diagnosed in layer hens. Among these, amyloidosis, salmonellosis and colibacillosis were paramount. Neoplastic and protozoal hepatitis occurred more frequently in backyard poultry. The macroscopic examination in association with histopathology enabled the diagnosis in 59% of the cases. In cases of bacterial hepatitis, the association of the histopathological examination with the bacteriological analyses was essential for the definitive diagnosis of the etiology. The liver of poultry can be affected by a variety of systemic causes, being the primary target of several etiologies. Considering bacterial and toxic hepatitis in commercial poultry, the etiological diagnosis is highly important, considering the risk for public health, despite the obvious importance due to the productivity losses and condemnation at food processing.